Development of Fungal Anti-Attachment Inks for 3D Printed Medical Devices - Yong, Ling Xin (2022)
Fungal infections of medical devices caused by Candida albicans alone have resulted in up to 50 % mortality. Utilisation of fungal-resistant polymer could reduce mortality rate and reduce complications in patient’s health from frequent changes of medical devices. At present, Polydimethylsiloxane (PDMS) is commonly used due to its biocompatibility, excellent temperature and chemical resistance, and its good mechanical and moulding properties. However, in many of its biomedical applications such as voice prostheses and urinary catheters, PDMS can attract yeasts that form biofilms which trigger infections in device users. This is especially so for indwelling voice prostheses as there are currently no commercially available antimicrobial options and the device must be changed every few months.